Hepatitis B Virus, Hepatitis C Virus Markers and Serum Alanine Amino-Transferase (ALT) Levels, in a Young Adult Population of Sylhet District - Perveen, Irin; Saha, Madhusudan; Dhar, Kishore Kumar; Islam, Md Shamsul (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Objective: To find out the seroprevalence of the hepatitis B and C viruses in a young adult population along with estimation of aminotransferase levels. And so as to increase the awareness and augment preventive measures against these viral hepatitis related morbidity. Methods: A total of 2611 apparently healthy young adults were screened from January 2010 to December 2010 at a Medical Checkup center of Sylhet for hepatitis B surface antigen (HBsAg), hepatitis C virus antibody (anti HCV), alanine aminotransferase (ALT) and aspertate aminotransferase (AST) levels. Results: Out of 2611 subjects 2536(97.1%) were male and 75(2.9%) were female with comparable mean ages (29.08 vs. 30.6 years, P .056). A total of 77(3.0%) men were HBsAg positive and only four (0.16%) men were positive for anti HCV. Women were all negative for HBsAg or anti HCV. None had co-infection with HBV and HCV. Mean ALT and AST levels of study population were 31.85 I.U./L and 26.18 I.U./L respectively and were not found to vary with age and sex. Mean ALT levels were more in in HBsAg positive cases (42.03 I.U/L vs. 31.5 I.U./L, P .000) and HCV infected cases (49 I.U./L vs. 31.51 I.U./L, P.000) than non-infected persons. Conclusion: Hepatitis B infection is of intermediate endemicity among young adults while hepatitis C virus infection is low among this group. Mean amino transferase levels were higher in asymptomatic infected persons in comparison to non-infected person. We suggest the need for revision of upper limit of normal for ALT in our population for early detection and treatment of liver diseases. J Bangladesh Coll Phys Surg 2016; 34(4): 199-205